Study of problem-based learning with questioning technique to promote choreography ability of dance students - Wang Di; Premjit Kajonpai Larsen; Rekha Arunwong (Journal of Green Learning, 2022)
The purposes of this research were to compare the dance design ability of students before and after exposed problem-based learning with questioning techniques, and to compare the dance design ability of students with 70% evaluation criteria. In this study, juniors majoring in dance choreography in Music College of Langfang Normal University were selected as the research. There were 20 students from one class were randomly selected. Research tools include achievement test and performance tests. The t-test for dependent and t-test for one sample were used for statistical analysis. The results showed that the dance design ability of these samples were effectively improved after the problem-based learning. They were significantly higher than the pre-test and for the dance design ability and the post-test scores, and higher than the criterion of 70% at the .05 level of statistics.